Literasi Kesehatan Digital sebagai Penentu Pelindung dan Strategis Kesehatan Remaja di Era Disinformasi: Systematic Review - Windi Nurdiana Utami; Tiara Amelia; Rohman Daka (Jurnal Dunia Kesmas, 2026)
Adolescents constitute a significant population group playing a crucial role in achieving sustainable development goals, yet they are increasingly exposed to health misinformation in the digital infodemic era. This study aims to synthesize evidence on digital health literacy as a protective factor against misinformation, its relationship with preventive health behaviors, and its role as a health promotion strategy among adolescents aged 9–21. This systematic review, following the 2020 PRISMA guidelines, uses a thematic synthesis approach to 16 empirical studies (2022–2026) from 10 countries identified through primary databases using the PICO framework. Results indicate that digital health literacy improves adolescents' ability to critically evaluate online health information, thereby reducing their vulnerability to misinformation. Digital health literacy is also significantly associated with preventive behaviors such as vaccination, hand hygiene, healthy eating, and physical activity. Furthermore, interactive, co-designed digital interventions have been shown to be effective in increasing knowledge, critical skills, and engagement. These findings confirm digital health literacy as a protective and strategic determinant in improving adolescent health in the digital era.